2004
DOI: 10.1021/jp036229t
|View full text |Cite
|
Sign up to set email alerts
|

M3+ Lanthanide Chloride Complexes in “Neutral” Room Temperature Ionic Liquids:  A Theoretical Study

Abstract: The solvation of MCl n 3- n lanthanide chloride salts (La3+, Eu3+, and Yb3+; n = 3, 6, and 8) is studied by molecular dynamics simulations in two room-temperature ionic liquids which are “neutral” (Lewis acidity):  [BMI][PF6] composed of 1-butyl-3-methyl-imidazolium+,PF6 - ions and [EMI][TCA] composed of 1-ethyl-3-methyl-imidazolium+,AlCl4 - ions. The simulations reveal the importance of the MCl6 3- complex, commonly observed in solid-state structures and in chloride-containing solutions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 67 publications
7
51
0
Order By: Relevance
“…[a] a [28,68] b [37] c [36,69] d [39] e [38] f [27] g [30] A [a] UA = united atom model; cc-pVTZ(-f) is a cc-pVTZ basis set with all the f functions removed.…”
Section: Partial Charges Used For the [C 4 C 1 Im]mentioning
confidence: 99%
“…[a] a [28,68] b [37] c [36,69] d [39] e [38] f [27] g [30] A [a] UA = united atom model; cc-pVTZ(-f) is a cc-pVTZ basis set with all the f functions removed.…”
Section: Partial Charges Used For the [C 4 C 1 Im]mentioning
confidence: 99%
“…It appears that the same holds true in ionothermal framework synthesis using transition metal acetates. This may be in part due to the ability of halide ionic liquids to form very stable complexes with metals, especially metal halides [46,47]. We explored several IL/metal acetate mixtures and found them to give mixed chain and 3D products (as discussed above) with the 3D phases favoured by longer heating times as observed by Rao et al [21] in the hydrothermal synthesis of zinc phosphates.…”
Section: Resultsmentioning
confidence: 81%
“…In a later study a number of force field models were examined and it was concluded that charges would need scaling before accurate mixing dynamics could be obtained. [25] The effects of charge scaling on solute-solvent interactions have also been examined; only minor effects on solvation patterns were determined after the point charges of a neutral solute were halved, [39] and thus it appears that for a solute the overall charge is more important than the internal charge distribution.…”
Section: Force Field Developmentmentioning
confidence: 99%